ANALYSIS OF SUPPLY COMPONENT OF BETA VALVE, BLEED VALVE AND PROPELLER REDUCTION GEARBOX - Ririn Isnawati (Vortex, 2020)
Maintenance  is  a  very  important  thing  to  do  in  order  to  keep  the  aircraft  in flightworthiness. One form of maintenance activity is the replacement of components that have been damaged (failed). Inventory components can not be a avided because to get it can not be done  suddenly  while  for  those  needs  can  occur  suddenly.  Thus,  it  is  necessary  to  plan  the number  of  component  inventories  so  that  smooth  production  is  maintained.  Efforts  to  solve these problems use the Mean Time Between Removal (MTBR) equation. Where MTBR is used to determine inventory levels and component replacement scheduling. In addition, the MTBR is a formula or model to determine how much inventory per year will minimize the depletion of  inventory  in  the depository  and  for  estimating  component  replacement.  From  the  data processingof the G120 TP-A GROB, the number of component inventories in one year is based on  the  age  of  components  from  manufacture (MTBRStandard),  among  others:  10  Beta  Valve Components, 17 Bleed Valve Components, and 13 Propeller Reduction Gearbox Components